Empirically-derived subgroups of Facebook users and their association with personality characteristics: a Latent Class Analysis. (September 2018) - Lo Coco, Gianluca; Maiorana, Angela; Mirisola, Alberto; Salerno, Laura; Boca, Stefano; Profita, Gabriele
Abstract: In recent years, considerable research effort has been directed at the identification of relationships between psychological variables and Facebook usage indicators. However, the identification of homogeneous subgroups of individuals based on similar Facebook usage characteristics still presents a challenge. This study aims: (1) to empirically determine homogeneous groups of Facebook users based on variables regarding their personal experience on Facebook, by using a Latent Class Analysis; and (2) to examine the association between an individual's personality and interpersonal characteristics and the empirically-derived profiles of Facebook usage. Eight hundred and eleven Facebook users (aged from 17 to 61 years) provided data on personality traits, self-esteem, interpersonal difficulties, attachment styles, preference for online social interaction and information on general Facebook use. We found that a three-class model (Mild-users, Committed to Facebook, and Online Socially-Oriented groups) fitted well with our data. Individuals in the Online Socially-Oriented group reported greater openness to experience as well as a greater preference for online social interaction, whereas the individuals in the Committed to Facebook group showed high self-esteem, extraversion and need for approval, as well as low emotional stability. The results of this study provided a more comprehensive picture of individual characteristics associated with the different profiles of Facebook usage. Highlights: The association between Facebook use and individual characteristics is unclear. Three different subtypes of Facebook users were identified. The Committed to Facebook showed high extraversion but low emotional stability. The Online Socially-Oriented reported high openness and online interaction. The Mild-users showed lower extraversion and self-esteem.